Optimization of the Solid-state Fermentation Process for Morchella esculenta Fermented Wheat and Analysis of Its Nutritional Components, Physicochemical Properties and Antioxidant Activity - Dandan GU; Xue DONG; Jinxiu ZHANG; Xiaoru WANG; Zongshuo ZHAO; Li'an WANG (Shipin gongye ke-ji)
Using wheat grains as the raw material and Morchella esculenta as the fermentation strain, fungus fermented wheat (FFW) was prepared through a solid-state fermentation process. Crude fiber content and non-starch polysaccharide (NSP) content were used as evaluation indicators, while factors such as the material to liquid ratio, initial pH of the substrate, inoculum amount, and fermentation duration were investigated. An orthogonal experimental design was utilized to optimize the preparation process of FFW, and the nutritional composition, physicochemical properties and antioxidant activity were analyzed. The results showed that the optimal fermentation conditions were a material to liquid ratio of 1:0.9 (g:mL), an initial substrate pH of 7.0, an inoculum amount of 5 inoculum blocks (each with a diameter of 0.8 cm), and a fermentation duration of 10 days. Under these conditions, the crude fiber content of FFW was 4.09%, and the NSP content was 9.31%. Compared to unfermented wheat, the surface of FFW developed holes, increased grooves, and deepened wrinkles. The protein content of FFW increased by 78.79%, while the carbohydrate content decreased by 17.79%. The soluble dietary fiber (SDF) increased by 43.70%, whereas the insoluble dietary fiber (IDF) decreased by 19.24%, with no significant change in the total dietary fiber (TDF). Additionally, the water-holding capacity, unsaturated fatty acid adsorption capacity, saturated fatty acid adsorption capacity, and swelling capacity of FFW increased by 77.84%, 11.49%, 25.00%, and 26.00%, respectively. Under simulated conditions of the human stomach and intestine, the cholesterol adsorption rate increased by 86.29% and 290.14%, respectively. The total antioxidant activity, DPPH radical scavenging rate, superoxide anion radical scavenging rate, and hydroxyl radical scavenging rate of FFW increased by 41.29%, 14.54%, 490.68%, and 10.80%, respectively. In summary, FFW prepared by this process significantly enhances the nutritional value, physicochemical properties, and antioxidant activity of wheat, providing a theoretical basis for the development of new products based on FFW.